Integration of Offline Digital Technology and Local Wisdom in Early Childhood Speaking Skills Development - Hadija Alaydrus, Siti; Idrus, Idrus; Hasrul, Hasrul; Lausu, Suandi; Asrianti, Asrianti (Journal of English Language and Education, 2026)
This study aims to describe the integration of offline digital technology and local wisdom in developing the speaking skills of early childhood learners at TK ABA 2 Ova, Palu. The research focuses on how simple digital media combined with elements of local culture, such as folklore and traditional games, contribute to the improvement of children’s verbal abilities. A qualitative descriptive approach was employed, with data collected through observation, interviews with teachers and parents, and documentation of children’s learning activities. Data analysis was conducted through the stages of data reduction, display, and conclusion drawing, following the interactive model proposed by Miles and Huberman. The findings reveal that the application of offline digital media incorporating local stories and traditional games has a positive impact on children’s language development. It enhances vocabulary mastery, sentence structure, fluency, confidence, and semantic accuracy in speech. Children exposed to culturally based digital media demonstrated higher levels of verbal participation and idea expression, while traditional games fostered natural spontaneity and interactive communication. The main supporting factors included teacher facilitation and collaboration between school and family, whereas the primary challenge was the limited availability of digital facilities. Overall, the integration of simple digital technology and local wisdom proved effective in enriching children’s linguistic experiences while strengthening cultural values within the language learning process.